On the Use of Graphene Nanosheets for Drug Delivery: A Case Study of Cisplatin and Some of Its Analogs - Mahmoud A. A. Ibrahim; Manar H. A. Hamad; Amna H. M. Mahmoud; Gamal A. H. Mekhemer; Shaban R. M. Sayed; Mohamed K. Abd El-Rahman; Peter A. Sidhom; Eslam Dabbish; Tamer Shoeib (MDPI AG, 2023)
Graphene (GN) nanosheets have been widely exploited in biomedical applications as potential nanocarriers for various drugs due to their distinct physical and chemical properties. In this regard, the adsorption behavior of cisplatin (cisPtCl2) and some of its analogs on a GN nanosheet was investigated in perpendicular and parallel configurations by using density functional theory (DFT). According to the findings, the most significant negative adsorption energies (Eads) within the cisPtX2⋯GN complexes (where X = Cl, Br, and I) were observed for the parallel configuration, with values up to -25.67 kcal/mol at the H@GN site. Within the perpendicular configuration of the cisPtX2⋯GN complexes, three orientations were investigated for the adsorption process, namely, X/X, X/NH3, and NH3/NH3. The negative Eads values of the cisPtX2⋯GN complexes increased with the increasing atomic weight of the halogen atom. The Br@GN site showed the largest negative Eads values for the cisPtX2⋯GN complexes in the perpendicular configuration. The Bader charge transfer outcomes highlighted the electron-accepting properties of cisPtI2 within the cisPtI2⋯GN complexes in both configurations. The electron-donating character of the GN nanosheet increased as the electronegativity of the halogen atom increased. The band structure and density of state plots revealed the occurrence of the physical adsorption of the cisPtX2 on the GN nanosheet, which was indicated by the appearance of new bands and peaks. Based on the solvent effect outlines, the negative Eads values generally decreased after the adsorption process in a water medium. The recovery time results were in line with the Eads findings, where the cisPtI2 in the parallel configuration took the longest time to be desorbed from the GN nanosheet with values of 61.6 × 108 ms at 298.15 K. The findings of this study provide better insights into the utilization of GN nanosheets in drug delivery applications.